Career Adaptability and Retention Satisfaction among Full-Time, Non-tenure Track Faculty Researchers in Academic Medicine - Hobson, Tara (ProQuest Dissertations & Theses, 2022)
With the landscape of higher education changing, a new culture for faculty on campuses includes significant variation in employment types among faculty members. Regardless of institution type, the number of tenure track roles is declining, and non-tenure track positions are increasing. These positions often operate on employment contracts, do not have the same protected academic freedoms as tenure track positions, lack institutional support to promote individual success in job performance, and fall subject to state laws relating to termination. While non-tenure track faculty positions continue to see immense growth, the current structure of non-tenure track faculty researcher positions is challenging for personal career advancement. This study had two purposes: first, to better understand the relationship between career adaptability and retention satisfaction, and second, to examine the unique career experiences of minoritized faculty in this field based on gender, race, and ethnicity. This quantitative study tested the associations among career adaptability and retention satisfaction factors. Further, the study assessed whether there were differences in career adaptability subscales and retention satisfaction between men and women, and if there were differences in career adaptability subscales and retention satisfaction between White faculty and Historically Marginalized faculty in academic medicine and the biomedical sciences. This study collected data from 139 non-tenure track faculty working in research at Research 1 medical schools in the United States. Responses on career experiences were collected using the Career Adapt-Abilities Scale (CAAS; Savickas & Porfeli, 2012) and the Retention Factor Measurement Scale (RFMS; Döckel et al., 2006). The 24-item CAAS measures concern, control, curiosity, and confidence. The RFMS is a multifactorial self-rating scale that includes 35 items that measure retention satisfaction factors, including compensation, job characteristics, training and development opportunities, supervisor support, career opportunities, and work–life balance.The canonical correlation examining the relationship between career adaptability and retention satisfaction was not statistically significant. Also, the MANOVAS comparing women and men on career adaptability and on retention satisfaction were not statistically significant. Similarly, the MANOVAS comparing faculty who identify as White and faculty who identify as Historically Marginalized were not statistically significant. While the findings were not statistically significant, these research questions and results add to the body of research on faculty development in academic medicine, non-tenure track faculty appointments, career adaptability, and retention satisfaction.